Estimation of Land Surface Temperature using GIS and MATLAB - Rajeshwari, A; Mani, N.D (International Journal of Computer Sciences and Engineering, 2025)
Land Surface Temperature (LST) is the skin temperature of the earth surface. And it is found that the value of LST will be high in settlement regions and low in area under green cover. The amount of green cover is reducing day by day which leads to higher LST. Hence in this paper LST was calculated for in and around Dindigul City. Satellite image provides information about thermal reflection. Satellite image processing is usually done in GIS and Digital Image Processing Software, whereas the output thus processed was compared with the result derived from Matlab software. From the analysis it is evident that Matlab can also be utilised for satellite image processing also. To calculate LST Split-Window Algorithm has been used. The output reveals that the LST estimated using both the software are nearly correlated. The slight difference is due to data type conversion in Matlab.